2020
DOI: 10.3390/publications8010004
|View full text |Cite
|
Sign up to set email alerts
|

How Many Papers Should Scientists Be Reviewing? An Analysis Using Verified Peer Review Reports

Abstract: The current peer review system is under stress from ever increasing numbers of publications, the proliferation of open-access journals and an apparent difficulty in obtaining high-quality reviews in due time. At its core, this issue may be caused by scientists insufficiently prioritising reviewing. Perhaps this low prioritisation is due to a lack of understanding on how many reviews need to be conducted by researchers to balance the peer review process. I obtained verified peer review data from 142 journals ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Considering the increasing difficulty in obtaining timely high‐quality reviews, Raoult (2020) proposed that scientists should conduct at least one review per publication they produced in order to ensure the peer review system continues to function. The median review to publication ratio of all the four groups of reviewers were less than 1, but each group had reviewers that had a ratio larger than 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the increasing difficulty in obtaining timely high‐quality reviews, Raoult (2020) proposed that scientists should conduct at least one review per publication they produced in order to ensure the peer review system continues to function. The median review to publication ratio of all the four groups of reviewers were less than 1, but each group had reviewers that had a ratio larger than 1.…”
Section: Resultsmentioning
confidence: 99%
“…This study selected the top 1,000 Publons partner journals that have received the largest number of verified reviews during a 12 months period (February 2019–February 2020) in the Research field of Medicine (Raoult, 2020). Journals were then selected that have an official Partnership with Publons to reduce bias.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that sense, Publons emerged as a platform to "reward" academics for their time and efforts, and as a form of public recognition. 6 However, such recognition can be perceived by some academics as a pennies-on-the-dollar scheme because even if demand for reviewers is high, the pool of available academics to complete the task is large, although this sink-and-demand dynamic might change if more academic journals enter the market, placing additional pressure on the same peer pool [20]. Pomponi et al [21] found that Publons' marketing approach was promotional, appealing to academics' vanity and sense of self-worth rather than on peer review-related novelty, also noting that most reviewers emerged from the US, India, then China.…”
Section: Publons' Role In Peer Review Rewards: a Critical Perspectivementioning
confidence: 99%
“…Four Royal Society journals (Proceedings A, B, Royal Society Open Science and Open Biology) also continue to claim to be participating in the Publons TPR program and using OPR by publishing reviewers' reports, decision letters and responses alongside published articles. 20 The Royal Society encourages reviewers to disclose their names to authors, but this is a voluntary choice. Moreover, the publisher does not permit the publication of peer review information for rejected papers.…”
Section: The "Pitfalls" Of Transparent Peer Review Pilotsmentioning
confidence: 99%